OUT-SOURCING PROJECT STRATEGIC JUSTIFICATION TOOLS AND METHODS FOR UP-TO-DATE COMPANY MANAGEMENT SYSTEMS - N. I. Strikh (Модернизация, инновация, развитие, 2016)
The term out-sourcing signifies signing an agreement with some external organization on performing certain management functions (accounting, communication, computer networks, etc.). Out-sourcing is an important instrument of company restructuring by improving its management system. Main methodological approaches to make decision on out-sourcing on the basis of simulation are discussed. Strategic substantiation of out-sourcing projects is proposed to be carried out on the basis of strategic positioning method developed by M. Porter.